Integrated control of water hyacinth [Pontederia crassipes Mart. (Solms) (Pontederiaceae)] - Mnciva, Siyasanga Tracy (Rhodes University, 2026)
Pontederia crassipes Mart. (Pontederiaceae) poses serious ecological and economic problems in freshwater ecosystems. Herbicidal and biological control are two conventional methods of managing this aggressive weed. When used separately, these strategies have drawbacks: biological control alone is not perceived to work quickly enough, and herbicides present non-target environmental hazards. Careful integration of herbicides with biocontrol agents may potentially lead to synergistic effects in managing this invasive aquatic weed. Herbicide compatibility with biological control agents remains unclear and warrants further investigation. The current study investigated the impact of integrating a biocontrol agent, Megamelus scutellaris Berg (Hemiptera: Delphacidae), and sublethal concentrations of selected glyphosate-based herbicides for P. crassipes control. Firstly, laboratory experiments were carried out to identify sublethal concentrations of three routinely used glyphosate-based herbicides (GBH) on P. crassipes plants. The results showed that sublethal concentrations of Kilo Max (0.4%) and Seismic (0.75%) herbicides reduced the vegetative growth and biomass of P. crassipes plants. The effect of these sublethal concentrations on M. scutellaris populations was then assessed by recording the number of surviving insects on treated plants, where significantly more insects were recorded from the plants treated with sublethal concentration of Kilo Max (0.4%). These results highlighted that the sublethal herbicide concentrations allowed P. crassipes to persist but not reproduce and suggested that biochemical changes in the sprayed plants might be favouring the population growth of M. scutellaris. The effects of sublethal concentrations of herbicides on the biochemistry of P. crassipes plants were therefore assessed by isolating the nutritional plant metabolites in sprayed and unsprayed plants. Colorimetric analyses of herbicide-treated and untreated leaves were performed to quantify carbohydrate, protein, and phenolic contents from the extracted compounds. The accumulation of carbohydrates and proteins in P. crassipes leaves increased in the first week following the application of a sublethal concentration of Kilo Max (0.4%), which could explain the increase in insect populations from the sprayed plants. The accumulation of metabolites in the sprayed plants suggests that the primary metabolism is induced by the sublethal herbicide application on P. crassipes leaves. Notably, the accumulation of carbohydrates such as sucrose is important for reducing the damage caused by herbicide stress in plants, as these soluble sugars act as osmoprotectants. The accumulation of metabolites in P. crassipes plants following sublethal herbicide sprays may affect the foraging and dispersal behaviour of M. scutellaris, thereby altering population dynamics where integrated control is used as a weed management tool. Mesocosm experiments investigated the dispersal patterns of M. scutellaris during sublethal herbicide treatments of Kilo Max (0.4%) and Seismic (0.75%) herbicides, where tubs containing sprayed and unsprayed P. crassipes plants were placed near mesocosms containing plants inoculated with M. scutellaris. M. scutellaris persisted on the sprayed plants for the first five weeks of the experiments and then dispersed to unsprayed plants when the conditions of the sprayed plants deteriorated. From these results, we can deduce that sublethal herbicide concentrations supported the development of M. scutellaris populations, however, the death of the host plant caused their dispersal to neighbouring unsprayed plants. Sprayed plant populations decreased significantly, suggesting that the combined effects of sublethal herbicide stress and herbivory by M. scutellaris reduced P. crassipes vigour. Similar results were observed under field conditions, where M. scutellaris were released in herbicide-sprayed sites that were paired with unsprayed sites. The insects migrated from herbicide sprayed to unsprayed areas, however, their efficacy on unsprayed P. crassipes plants was inadequate as the insect population numbers were reduced. These studies provided important insights into the potential safe integration of sublethal herbicide concentrations and biocontrol agents for weed management, indicating that sublethal herbicide concentrations can enhance the efficacy of biocontrol agents and promote effective weed suppression while minimising environmental pollution. However, small biocontrol populations in the field suggest that multiple releases of M. scutellaris in large numbers to inundate P. crassipes infestations should be implemented in future integrated management studies involving sublethal herbicide applications, as this is most likely to lead to yield successful control of the plants.
interactions between the biological control agent, Megamelus scutellaris Berg (Hemiptera: Delphacidae), and selected sublethal glyphosate-based herbicide applications, in South Africa
Keywords: Uncatalogued